2023
DOI: 10.1186/s40560-023-00659-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of urinary C–C motif chemokine ligand 14 (CCL14) and first-generation urinary biomarkers for predicting renal recovery from acute kidney injury: a prospective exploratory study

Abstract: Background Acute kidney injury (AKI) is a frequent syndrome in the intensive care unit (ICU). AKI patients with kidney function recovery have better short-term and long-term prognoses compared with those with non-recovery. Numerous studies focus on biomarkers to distinguish them. To better understand the predictive performance of urinary biomarkers of renal recovery in patients with AKI, we evaluated C–C motif chemokine ligand 14 (CCL14) and two first-generation biomarkers (cell cycle arrest bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…First, the meta-analysis was hindered by the small sample sizes of most studies, leading to high heterogeneity. Furthermore, while the majority of studies enrolled patients with stage 2 or 3 AKI, two studies included a substantial number of patients with stage 1 AKI or non-AKI [ 19 , 24 ]. This heterogeneity of the patient cohorts in the included studies further contributed to the overall heterogeneity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…First, the meta-analysis was hindered by the small sample sizes of most studies, leading to high heterogeneity. Furthermore, while the majority of studies enrolled patients with stage 2 or 3 AKI, two studies included a substantial number of patients with stage 1 AKI or non-AKI [ 19 , 24 ]. This heterogeneity of the patient cohorts in the included studies further contributed to the overall heterogeneity of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that [TIMP-2]*[IGFBP7] (product of TIMP2 and IGFBP7) levels are significantly elevated in patients with AKI, and their predictive ability outperforms that of individual biomarkers alone [ 23 ]. In addition, others have demonstrated the potential of [TIMP-2]*[IGFBP7] in assessing renal recovery status [ 24 , 25 ]. Therefore, the current study aimed to investigate whether [TIMP-2]*[IGFBP7] is a reliable predictor of renal non-recovery in older adults with AKI over seven days.…”
Section: Introductionmentioning
confidence: 99%